METHODS FOR CONSTRUCTION OF ODD NUMBER POINTED POLYGONS - Daniel Dobre (Journal of Industrial Design and Engineering Graphics, 2016)
The purpose of this paper is to present methods for constructing of polygons with an odd number of sides, although some of them may not be built only with compass and straightedge. Odd pointed polygons are difficult to construct accurately, though there are relatively simple ways of making a good approximation which are accurate within the normal working tolerances of design practitioners. The paper illustrates rather complicated constructions to produce unconstructible polygons with an odd number of sides, constructions that are particularly helpful for engineers, architects and designers. All methods presented in this paper provide practice in geometric representations.